Recycling the disabled : Army, medicine, and modernity in WWI Germany - Perry, Heather R. (Book collections on Project MUSE., 2014)
This book examines the 'medical organisation' of Imperial Germany for total war. Faced with mounting casualties and a growing labour shortage, German military, industrial and governmental officials turned to medical experts for assistance in the total mobilisation of society. Through an investigation of developments in orthopaedic medicine, prosthetic technology, military medical organisation and the cultural history of disability, Heather Perry reveals how the pressures of modern industrial warfare not only transformed medical ideas and treatments for injured soldiers, but also transformed social and cultural expectations of the disabled body - expectations that long outlasted the war. This book is ideal for scholars and students interested in war, medicine, disability, science and technology, and modern Germany.